Exploring Sarcasm among Netizens on Instagram: A Social Media Phenomenon - Damayanti, Rini; Kaswadi, Kaswadi (NOBEL: Journal of Literature and Language Teaching, 2024)
This paper explores the prevalent use of sarcasm among Indonesian Instagram users, particularly on the @Insertlive account and its link to cyberbullying. This qualitative study, adopting Keraf’s sarcasm function theory, identifies different types of sarcasm and how offensive language affects communication and social norms in social media. The study reveals different sarcasm functions like rejection, prohibition, information, and vulgarities, indicating that sarcasm is widely used in online communication. On the one hand, sarcasm is a means of laughter and togetherness; on the other hand, however, it is a hostile strategy to insult and criticize. This paper highlights the social benefits of constructive sarcasm compared to its potential harms that may lead to cyberbullying. It is suggested that social media should improve the moderation features and promote positive comments. Besides, future research could examine the effect of sarcasm on the psychological state of targets and observe cultural differences in the use of sarcasm across various platforms.